2021
DOI: 10.3390/cancers13205082
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Factors Differentially Affect the Recruitment and Plasticity of Neutrophils

Abstract: Neutrophils play a key role in cancer biology. In contrast to circulating normal-density neutrophils (NDN), the amount of low-density neutrophils (LDN) significantly increases with tumor progression. The correlation between these neutrophil subpopulations and intratumoral neutrophils (TANs) is still under debate. Using 4T1 (breast) and AB12 (mesothelioma) tumor models, we aimed to elucidate the source of TANs and to assess the mechanisms driving neutrophils’ plasticity in cancer. Both NDN and LDN were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
(97 reference statements)
1
11
0
Order By: Relevance
“…Injection of isolated NDN to recipient LKRM tumor-bearing mice resulted in decreased tumor growth and a significant response, whereas injection of LDN had no effect on tumor growth ( Figure 4 ). Both NDN and LDN adoptive transfers induced a tendency to increase the percentage of TAN in the tumor ( Figure 4 ), supporting our recent findings demonstrating the ability of both NDN and LDN to infiltrate tumors in vivo [ 47 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Injection of isolated NDN to recipient LKRM tumor-bearing mice resulted in decreased tumor growth and a significant response, whereas injection of LDN had no effect on tumor growth ( Figure 4 ). Both NDN and LDN adoptive transfers induced a tendency to increase the percentage of TAN in the tumor ( Figure 4 ), supporting our recent findings demonstrating the ability of both NDN and LDN to infiltrate tumors in vivo [ 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…We could not find, however, clear changes induced by blocking PD-L1 in vitro in the functions of LDN and TAN we tested. Since we have recently shown that NDN can change in vivo to both LDN and TAN [ 47 ], it is possible that the changes found in the NDN functions are eventually seen in the other neutrophils’ subpopulations in vivo, affecting the results of ICI. In that context, it is important to remember that high levels of PD-L1 in the tumor is a well-known biomarker for the efficacy of ICI [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of CXCR2 and its ligands in neutrophil activation and maturation in the tumor context is still discussed. CXCL1 induced neutrophil transition from NDN to a lowdensity state (LD-NDN) with a phenotype similar to that of LDN, which could promote tumor development [141]. In addition, combined inhibition of CXCR2 and SHP2 in nonsmall cell lung cancer (NSCLC) models, selectively targeted a population of TANs with an immunosuppressive phenotype [142].…”
Section: Role Of Chemokines In Neutrophil Activities In Cancermentioning
confidence: 99%
“…Therefore, based on the available information of neu phil involvement in breast tumor progression, it is reasonable to hypothesize that the trophil infiltration and activation within a primary TIME could, at least in part, med the metastatic cascade of the brain-tropic breast tumor cells (schematically shown in ure 1). However, a more fundamental question that remains to be answered is: how would the neutrophil activity and plasticity within a primary TIME be regulated differently [50], depending on the existence of intrinsic differences in the inflammatory signals expressed, by the pro-brain metastatic subtypes present within the parental breast cancer (PBC) [51]?…”
Section: Introductionmentioning
confidence: 99%